Dynamic transnational inter-ecosystem framework for smart and inclusive age-friendly environments: The Transnational Local-Sphere Model - van Boekel, Dieuwertje; Cabrita, Miriam; van Staalduinen, Wilhelmina; do Rosário Cabrita, Maria; Masiero, Francesca; Uriarte, Silvia Urra; Georgoulis, Dimitris; Dantas, Carina (Technium Social Sciences Journal, 2024)
The demographic change calls for the creation of age-friendly environments that result from the collaboration between several fields. Previous initiatives fostering age-friendly environments often had less-than-desired impact or reach due to financial and bureaucratic constraints. Additionally, territory-specific standards and needs hinder the replication of good practices. Based on a mixed-methods approach combining a narrative review of knowledge models followed by expert consultation, we propose a framework to maximise the sustainability of Smart Healthy Age-friendly Environment (SHAFE) initiatives by connecting local ecosystems and stakeholders, including underrepresented entities, and thus promote sustainable business models, to ensure the replicability, scalability, and sustainability – the Transnational Local-sphere Model. This social innovation framework goes beyond previously established helix frameworks, by incorporating fresh ideas on democratic policy making, transnational spanning, and inter-ecosystem collaboration, as well as emphasising the role of institutions, stakeholders, networks, and principles. The collaboration and competition between the different stakeholders ensure a value-driven, cost-effective, and inclusive intervention, maximising impact. The Transnational Local-Sphere Model can also be applied in the development of other social innovation initiatives that benefit a usercentred multi-stakeholder inter-ecosystem approach.